2021
DOI: 10.3389/fimmu.2021.631450
|View full text |Cite
|
Sign up to set email alerts
|

LncRNATUG1 Facilitates Th2 Cell Differentiation by Targeting the miR-29c/B7-H3 Axis on Macrophages

Abstract: The role of long non-coding RNAs (lncRNA) in asthma remains unclear. In this study, we examined the role of long non-coding RNA taurine upregulated 1 (lncRNA TUG1) in asthma. We found that lncRNA TUG1 is one of the differentially expressed lncRNAs in the monocytes of asthmatic children and is associated with Th cell differentiation. LncRNA TUG1 and miR-29c are mainly distributed in the cytoplasm of macrophages. Our data suggested that lncRNA TUG1 increased in macrophages stimulated by House Dust Mite in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…By performing in vitro experiments on macrophages, they demonstrated that TUG1 sponges microRNA-29c, which has been linked to Th2 cell differentiation. 56 By using a rat model, Lin et al studied the function of TUG1 in asthma. 57 TUG1 was upregulated in the ASMCs of an asthma M2 macrophage activation 75 ASMC, airway smooth muscle cell; lncRNA, long non-coding RNA; PBMC, peripheral blood mononuclear cell.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
See 1 more Smart Citation
“…By performing in vitro experiments on macrophages, they demonstrated that TUG1 sponges microRNA-29c, which has been linked to Th2 cell differentiation. 56 By using a rat model, Lin et al studied the function of TUG1 in asthma. 57 TUG1 was upregulated in the ASMCs of an asthma M2 macrophage activation 75 ASMC, airway smooth muscle cell; lncRNA, long non-coding RNA; PBMC, peripheral blood mononuclear cell.…”
Section: Metastasis-associated Lung Adenocarcinoma Transcript 1 (Malat1)mentioning
confidence: 99%
“…Sun et al observed that TUG1 is differentially expressed in monocytes of children with asthma. By performing in vitro experiments on macrophages, they demonstrated that TUG1 sponges microRNA-29c, which has been linked to Th2 cell differentiation 56…”
Section: Functional Role Of Lncrnas In Asthmamentioning
confidence: 99%
“…LncRNAs and miRNAs alone have been shown to play regulatory roles in asthma by regulating CD4 + T-cell function ( Wang et al, 2021c ). Notably, three studies observed a novel regulatory role of lncRNAs targeting miRNAs in regulating the Th1/Th2 balance ( Liang and Tang, 2020 ; Wei et al, 2020 ; Sun et al, 2021 ). For example, Sun et al ( Sun et al, 2021 ) observed that TUG1 is differentially expressed in the monocytes of asthmatic children.…”
Section: Lncrna–mirna Interaction In Chronic Inflammatory Airway Dise...mentioning
confidence: 99%
“…Notably, three studies observed a novel regulatory role of lncRNAs targeting miRNAs in regulating the Th1/Th2 balance ( Liang and Tang, 2020 ; Wei et al, 2020 ; Sun et al, 2021 ). For example, Sun et al ( Sun et al, 2021 ) observed that TUG1 is differentially expressed in the monocytes of asthmatic children. In further in vitro experiments on macrophages treated with house dust mites, they demonstrated that TUG1 could regulate B7-H3 expression in macrophages by sponging miR-29c, which then controls Th2 differentiation, providing novel potential diagnostic biomarkers and therapeutic targets for asthma.…”
Section: Lncrna–mirna Interaction In Chronic Inflammatory Airway Dise...mentioning
confidence: 99%
“…They play different regulatory roles by serving as different functional molecules, such as signals, decoys, guides, and scaffolds in multiple tumor cellular processes [ 22 , 72 ]. In recent studies, mounting evidence indicates that the lncRNA-miRNA-mRNA axis is present in cancers [ 73 , 74 , 75 , 76 , 77 ]. LncRNAs can mediate competitive mRNAs crosstalk by sharing microRNA response elements (MREs), which are also known as competing endogenous RNA (ceRNA) regulatory network mechanisms.…”
Section: Pcat6 Promotes Cancer Progression By Cerna Mechanismsmentioning
confidence: 99%